Etika dan Sopan Santun Remaja dalam Penggunaan Media Sosial di Era Globalisasi - Heriani, Avira; F, Firman; Sukma, Dina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Globalization has had a significant impact on the development of technology, especially social media. Teenagers as the main users of social media face challenges in maintaining ethics and manners. This study aims to identify the level of awareness of ethics and manners of teenagers in using social media. The method used is a literature study with an analysis of various relevant literature. The results of the study indicate that although most teenagers understand the importance of ethics, their practice still requires further guidance. This article provides practical recommendations to increase adolescents' ethical awareness in interacting in cyberspace.